Merdeka Belajar-Kampus Merdeka: Peluang Media Digital Dalam Pembelajaran Sejarah Publik di Era Globalisasi - Herdin Muhtarom (Program Studi Pendidikan Sejarah Universitas Riau, 2022)
The development of the times will have a positive or negative impact, especially in developments in the world of education, there are several positive and negative things that are felt in the world of education in the era of globalization. Technological developments will have an influence on the learning components, especially in history learning which can shape the character of students. Therefore, there is a need for a good analytical process for the development of technology used when learning history, so that students can understand the context of learning history to shape character in the era of globalization. In this study, the authors used qualitative research methods through a literature study approach. In learning in the era of globalization, especially to implement the Merdeka-Merdeka Campus program, learning can take advantage of digital media opportunities as a means in the learning process, so that people can find out all information about events, especially those related to public history.